Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Development and characterisation of a novel complex triple cell culture model of the human alveolar epithelial barrier - Sarah M. Mitchell; Kirsty Meldrum; Joshua W. P. Bateman; Teresa D. Tetley; Shareen H. Doak; Martin J. D. Clift (In vitro models, 2024)
Owing to increased pressure from ethical groups and the public to avoid unnecessary animal testing, the need for new, responsive and biologically relevant in vitro models has surged. Models of the human alveolar epithelium are of particular interest since thorough investigations into air pollution and the effects of inhaled nanoparticles and e-cigarettes are needed. The lung is a crucial organ of interest due to potential exposures to endogenous material during occupational and ambient settings. Here, an in vitro model of the alveolar barrier has been created in preparation for use in the quasi-air liquid interface (qALI) and (aerosol) air–liquid interface (ALI) exposures. The model consists of an alveolar type 1-like cell line (TT1), an alveolar type 2-like cell line (NCI-H441) and a model of (alveolar) macrophages (dTHP-1). The model formulates a complex, multi-cellular system, cultured at the air–liquid interface, that mimics the apical layer of the alveolar epithelial region in the human lung. Characterisation data has shown that both TT1 and NCI-H441 epithelial cells are able to be cultured together in addition to dTHP-1 cells through imaging (morphology), pro-inflammatory response and viability measurements. This dataset also demonstrates evidence of a reasonable barrier created by the cell culture in comparison to negative controls. Furthermore, it shows that while maintaining a low baseline of (pro)-inflammatory mediator expression during normal conditions, the model is highly responsive to inflammatory stimuli. This model is proposed to be suitable for use in toxicology testing of inhaled exogenous agents.

Transferability and reproducibility of exposed air-liquid interface co-culture lung models - Hedwig M. Braakhuis; Eric R. Gremmer; Anne Bannuscher; Barbara Drasler; Sandeep Keshavan; Barbara Rothen-Rutishauser; Barbara Birk; Andreas Verlohner; Robert Landsiedel; Kirsty Meldrum; Shareen H. Doak; Martin J.D. Clift; et al. (NanoImpact, 2023)

Quantifying the contribution of matric suction on changes in stability and displacement rate of a translational landslide in glaciolacustrine clay - K. Sattler; D. Elwood; M. T. Hendry; D. Huntley; J. Holmes; P. B. Wilkinson; J. Chambers; S. Donohue; P. I. Meldrum; R. Macciotta; P. T. Bobrowsky (Landslides, 2021)

Application of multi-dimensional electrical resistivity tomography datasets to investigate a very slow-moving landslide near Ashcroft, British Columbia, Canada - D. Huntley; P. Bobrowsky; M. Hendry; R. Macciotta; D. Elwood; K. Sattler; M. Best; J. Chambers; P. Meldrum (Landslides, 2019)

Quantification of reactivated landslide behaviour using acoustic emission monitoring - N. Dixon; M. P. Spriggs; A. Smith; P. Meldrum; E. Haslam (Landslides, 2015)

3D ground model development for an active landslide in Lias mudrocks using geophysical, remote sensing and geotechnical methods - A. J. Merritt; J. E. Chambers; W. Murphy; P. B. Wilkinson; L. J. West; D. A. Gunn; P. I. Meldrum; M. Kirkham; N. Dixon (Landslides, 2014)

Persistent Increase of Blood Lead Level and Suppression of δ-ALAD Activity in Northern Bobwhite Quail Orally Dosed With Even a Single 2-mm Spent Lead Shot - S. D. Holladay; R. Kerr; J. P. Holladay; B. Meldrum; S. M. Williams; R. M. Gogal (Archives of Environmental Contamination and Toxicology, 2012)